Knowledge, attitudes, and practices of dentists in the Parañaque dental chapter regarding the management of patients with special health care needs - Laforteza, Denys Angeli P.; Mallari, Roselle Marie H.; Reyes, Louise Marie R.; Tan, Liza Maxine Kimberly G. (Department of Community Dentistry, University of the Philippines Manila, 2018)
INTRODUCTION: In the Philippines, around 1.44 million households include persons with special health care needs (SHCN). Metro Manila alone has around 167,000 individuals with a disability, most of whom are unable to access dental services. The objective of the study was to determine the knowledge, attitudes and practices of dentists in the Parañaque Dental Chapter regarding the management of patients with special health care needs.